STRATEGI PEMBERDAYAAN PEREMPUAN YANG BERUSAHA DARI PRODUK SAPI PERAH DI KABUPATEN ENREKANG - Yunarti, Nurhapsah, Nurhedah (Jurnal Ilmu dan Industri Peternakan, 2016)
ABSTRACT. The livestock sector was a sector which was very important in human life because it was associated with this sub-sector readiness in providing the animal food , which was known for the development and absolute growth . The research was conducted in Enrekang which was a center of dairy development in South Sulawesi province. The purpose of this study was to determine the profile , as well as factors inhibiting and supporting women's empowerment strategies that seek from dairy products . The data was collected through interviews and surveys to farmers who undertake the processing of dairy products as many as 83 people. Data processed by quantitative descriptive method . The results showed that on average respondents aged 31-50 years by level of education are mostly high school (SMA ) and up to 10 years of business experience . Factors supporting women struggling from dairy products was available land to grass , the raw materials are available and there are factors inhibiting government support was limited to the area of marketing, concentrate feed / bran expensive and difficult to obtain . Empowerment strategies that can be done for women struggling from dairy products was entrepreneurship training and support working capita.